Assessment of riparian ecosystem on amphibians along a Green Corridor in Oil Palm Plantation, Pasoh, Negeri Sembilan, Peninsular Malaysia - Norhayati, A.; Ehwan, N.; Okuda, T. (Universiti Kebangsaan Malaysia, 2014)
The large scale expansion of oil palm plantations nowadays bring huge negative impact on habitat destruction and loss of biodiversity, especially at Pasoh, Negeri Sembilan, Peninsular Malaysia. The monoculture system that was developed since the 1970s has suppressed biodiversity levels because of the lack of suitable microhabitats. In order to assess ecological remediation of plantation, a green corridor was established along Sg. Petekah at Felda Pasoh 2. The assessment was conducted from March to May 2012 at Sg. Petekah green corridor (SPGC) at Felda Pasoh 2 and Felda Pasoh 3 with no green corridor (FP3). Amphibians were sampled for species richness by using fenced pit fall traps and visual encounter surveys. Microhabitat selection of amphibians was identified to come up with recommendations for improvement. The low Shannon-Wiener diversity value, H’ at SPGC (1.82 ± 0.126) was obtained indicating that the remediation is yet to be achieved, but the H’ value was much lower at PF3 (0.62±0.2) indicating a positive projection of remediation. Microhabitat selection study indicated that each amphibian species tend to avoid overlapping of microhabitat based on specific guilds. Based on the results, the green corridor should be widened to allow space for foraging and territorial defence, planted not only with trees but also shrubs and herbs to improve the ground cover for the amphibians and also to include other animal groups, such as birds and mammals.